Investigation on the potential of local aggregates in producing high strengh concrete with fly ash / Narita Noh, Chew Fei Hua and Siti Zaidah Othman - Noh, Narita; Chew, Fei Ha; Othman, Siti Zaidah (RMI, 2014)
High strength concrete become more popular among engineers due to load carry by the building itself and the demand of skyscrapers being built in Malaysia. Generally, high strength concrete can be similar to normal concrete but with the presence of superplasticizer and cementatious material like fly ash, silica fume and granulated slag will boost the strength of concrete due to physical and chemical reaction within concrete itself. As the demand for high strength concrete increases in the local construction market, there is a need to develop high strength concrete using local aggregates. High strength concrete that is made from local aggregates will minimize construction cost, and at the same time results in more durable and lasting buildings. As the suitability of local aggregates for producing high strength concrete is not proved, there is a need for further investigation. In this study, fly ash will be used as cement replacement material that is mixed with local aggregates to develop high strength concrete. The objectives of this study are as follows: a) To optimize high strength mix design, using local aggregates with fly ash as partial replacement of cement b) To investigate the effect of using local aggregates in the properties of fresh and hardened high strength concrete Therefore, trial mixes using fly ash as different percentages of the total cementitious materials are made. Fresh and hardened concrete properties was done in laboratory. 10% of fly ash was recommandedin producing high strength by using local aggregate. The aim of this study is to help the construction industry and manufacturing market. If local aggregates are found to be suitable for producing high strength concrete, this means we are able to produce cheaper high strength concrete for the local construction market.